Daya Tetas Telur Ikan Uceng (Nemacheilus Fasciatus) pada Temperatur Berbeda di Laboratorium STIP Malang - Siswarini Siswarini; Sumariono Sumariono; Monica Tri Ayu Aedanie (Journal on Education, 2022)
The aim of this study was to determine the effect of temperature on the hatchability of uceng fish (Nemacheilus fasciatus). The experiment was carried out at the Laboratory of the College of Fisheries Sciences (STIP) Malang. Implementation in August 2022. Using a Completely Randomized Design (CRD) with a BNT 5% test, the treatment consists of 3 (three) stages with the following details; P1 (Treatment with a temperature of 25°C), P2 (Treatment with a temperature of 27°C) and P3 (Treatment with a temperature of 29°C) with 1 (one) control, namely K (control) without Heater (temperature 19-20°C )